The Uncertainty of Noise Composed of Separate Sound Events - MAKAREWICZ, Rufin; GOŁĘBIEWSKI, Roman (Archives of Acoustics, 2016)
Transportation noise is a main source of noise pollution. It is assumed that it consists of recognizable noise events which come from moving aircrafts, trains and boats. The noise of an isolated sound event is assessed by the sound exposure level, L_AE. Much legislation and many regulations and guidelines employ the A-weighted time-average sound level, L_Aeq,T, with the time interval T of one hour or longer. L_AE measurements enable an approximation of L_Aeq,T. The key point is the uncertainty of this approximation. It has been shown that an increase in the number of L_AE categories brings about a decrease in uncertainty. For illustrative purposes, L_AE measurements of aircrafts taking off and landing were carried out.